(untitled) (Research, Society and Development, 2022)
Forest fires in the Pantanal Mato-Grossense devastated about a third of the biome’s territory in 2020, which is the biggest fire recorded in this biome to date. In this work, we propose the analysis of the main governmental measures of a legal nature after the environmental tragedy that occurred in that biome, aiming to answer the following question: from the existing evidence regarding the causes of forest fires in the Pantanal Mato-grossense, the measures adopted by the Brazilian State are able to prevent forest fires and ensure the repair of environmental damage from the disaster that occurred? The measures adopted by the Brazilian government were raised through legislative consultation and news published on the official websites of the legislative and executive powers at the federal and state levels. The analysis of the measures was carried out considering preventive and combat actions in relation to the main causes of fires that occurred in the year 2020. Among the final considerations of the present study we have that the governmental measures may not only be insufficient to prevent new occurrences of fires, forest fires, but they can also put the biodiversity of the affected ecosystems at risk, as they start from the dubious assumption regarding the cause of the problem (biomass accumulation), neglecting the probable anthropic cause of the fires and the application of existing legal instruments that could be used to ensure the application of environmental law and also to prevent other incidents.